2014
DOI: 10.3906/sag-1302-92
|View full text |Cite
|
Sign up to set email alerts
|

New hemostatic agent: the effect of Ankaferd Blood Stopper on healing wounds in experimental skin incision model

Abstract: Turkey is of great importance for the biodiversity of genus Onobrychis Adans. and hosts 55 species that are adapted to dry and poor environments. This study was conducted to evaluate 35 Onobrychis taxa in terms of 1000-seed weight, germination percentage, mean germination time, and hard and swollen seeds and to determine the suitability of mechanical scarification for dormancy breaking in species with hard or impermeable seed coats. Seed dormancy was detected in 19 of the investigated species and 14 of the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…Most of these studies showed negative or ineffective effect on healing process similarly to our study results. In a study, Yüce et al [29] used experimental skin incision model in rabbits. They reported that ABS has negative effect on wound healing in the early periods while it has no negative effect on healing in the late periods.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies showed negative or ineffective effect on healing process similarly to our study results. In a study, Yüce et al [29] used experimental skin incision model in rabbits. They reported that ABS has negative effect on wound healing in the early periods while it has no negative effect on healing in the late periods.…”
Section: Discussionmentioning
confidence: 99%
“…ABS has been used as a local haemostatic agent in surgery, but it was also shown to promote healing (5,9). Its effects on soft-tissue healing have been investigated (17,(19)(20)(21), but not in a STZ model of diabetes. Therefore, the aim of the present study was to histologically assess the effects of ABS on collagen 4, blood GSH levels, and LPO to evaluate its potential effects in early-stage soft-tissue healing on STZtreated rats.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that ABS can be safely used for the repair of full-thickness wounds. Yüce et al also recommended ABS to promote wound healing (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3,7,[18][19][20] While many local hemostatic agents have been tested, no clear consensus exists regarding optimal hemorrhage control strategy for external bleeding. [1,4,8,9,[13][14][15][16][17]20,[24][25][26][27][28][29][30] However, Pusateri and Grissom [10,19] outlined ideal qualities of hemostatic agents for prehospital and battlefield use.…”
Section: Discussionmentioning
confidence: 99%